Apolipoprotein E-deficient rats develop atherosclerotic plaques in partially ligated carotid arteries. Issue 2 (December 2015) - Wei, Shujie; Zhang, Yan; Su, Linan; He, Kecheng; Wang, Qiang; Zhang, Yunrong; Yang, Dachun; Yang, Yongjian; Ma, Shuangtao
Abstract: Background: The goal of this study was to establish an apolipoprotein E-deficient (ApoE -/- ) rat model. Methods: The ApoE -/- rat was created by TALEN-mediated gene targeting in the genetic background of Sprague Dawley rat. Six-to eight-week-old male rats were used in the experiments (n = 10 in each group). Results: After fed with high-cholesterol diet (HCD) for 12 weeks, the ApoE -/- rats displayed typical dyslipidemia. In contrast, HCD failed to induce hypercholesterolemia in wild-type rats. However, there was no obvious atherosclerotic lesion in oil red O-stained en face aortas and the aortic root sections in both genetic types of rats. Interestingly, partial ligation caused the formation of plaques consist of lipid and macrophages in carotid arteries from ApoE -/- rats, but induced the neointimal hyperplasia in wild-type rats. Additionally, we found that HCD slightly increased the expression of adhesion molecules, while partial ligation dramatically upregulated these molecules. Conclusions: The ApoE -/- rat is a novel model for dyslipidemia and could also be used in the research of atherosclerosis.